Evaluation of adiponectin and calcium levels in patient's type II diabetics with obesity in Salah El-Din Province - Saleh Attallah Burjes Aljuboury; Nadia Ahmed Saleh Aljuboury (Tikrit Journal of Pure Science, 2022)
The association between obesity and type 2 diabetes may be partially mediated by altered adipose tissue secretion of adipokines. Adiponectin is an adipokines with anti-inflammatory and insulin-sensitive properties. It is a regulated low secretion in obesity, the concentrations of adiponectin and calcium in the blood serum of obese patients and type 2 diabetes will be estimated in Salah al-Din Province: Iraq, where the study included (90) samples (60) for patients with diabetes - type II and (30) from healthy subjects. The ages of the affected and healthy people ranged between 35-75 years. The results showed a significant increase at the level of probability (P≤0.01) in the level of adiponectin and calcium concentrations in patients with type 2 diabetes compared to healthy subjects, and through the results we obtained, adiponectin may play an important role in prevention of type 2 diabetes